Bond formation in diatomic transition metal hydrides: Insights from the analysis of domain‐averaged fermi holes. Issue 2 (24th May 2012) - Cooper, David L.; Ponec, Robert
Abstract The analysis of domain‐averaged Fermi holes (DAFHs) is used to provide detailed insights into the electron reorganization that accompanies the splitting of the bonding electron pairs in simple diatomic transition metal hydrides MH (M = Sc–Cr). The dissociation process is followed by monitoring the geometry dependence of the dominant DAFH functions, as well as their populations and overlaps. In addition to providing a highly appealing visual picture of the geometry‐induced changes in the bonding interactions, the DAFH approach clearly confirms the close link between the progress of the dissociation and the extent of electron sharing. The results of the various DAFH analyses straightforwardly reveal the anticipated close parallel in the nature of the MH bonds in the different systems studied, as well as the smooth character of the splitting of the associated shared electron pairs. In addition to a very basic resemblance between the different cases, subtle differences are revealed for individual systems. © 2012 Wiley Periodicals, Inc.